Local Government Participation in Health Promotion for Elderly : Amphoe Laplae, Changwat Uttaradit - Ubonsaad, Kittipong; Nargsanong, Thawatchai; Sutthatang, Napha; Somjuntha, Sompis; Junseng, Sairung; Kaujareunta, Phasuk; Prasarnsri, Sunisa (Journal of Health Science of Thailand, 2019)
Local government participation in health care and promotion is widely recognized as critical to success in Universal Health Care. This quantitative and qualitative research study was to assess participation of local governments organization and problems in health promotion for elderly in Amphoe Laplae, Changwat Uttaradit between January and June 2006. Community leaders and their members from 10 local government agencies. 111 participants from local government agencies, 65 members of health care teams and, 60 seniors were included in this study. The level participation questionnaire and focus group, in-depth interview, reviewing of field notes were used for data collection. Descriptive statistical analysis, content analysis and data triangulation were employed. It was reported that an average score of level of participation was 1.36 with the mean scores of 1.24, for evaluation, 1.31 for problems and needs, 1.44 for planning and project, implementation; and 1.46 for co-ordination respectively. In addition, the results revealed that problems were the lack of health care staff of local governments and limited knowledge and awareness related to health promotion for elderly. Moreover they believed that health of elderly was responsibility of health care team, and there was a lack of co-ordination among health care teams and members of the local governments. Their financial investment was devoted more on infrastructure development than human resource. Thriving on effective participation on this health issue, focus should be made on their knowledge management and increasing awareness while strengthening their ties and co-ordination with the health sector. Catering variances and limitations under different context, of many local authorities, development of participation model should be site specific.